The Academic Poster as a Resource to Enhance Cross-Curricular Competences in Higher Education - Martín Marchante, Beatriz (2022)
The objective of this study is to analyse the effectiveness of the academic poster as a pedagogical resource for the promotion of cross-curricular competences in engineering students. This study has been carried out with the participation of 402 students enrolled in different courses at the School of Design Engineering and the School of Telecommunication Engineering during the 2020-21 academic year. The results are drawn from pre-project and post-project questionnaires exploring the learner’s expectations and overall satisfaction upon completion. The authors also discuss project alignment with a number of cross-curricular competences. Although the degree of satisfaction in general has been slightly lower than the participants’ expectations, it should be noted that a high percentage of them value very positively the usefulness of the academic poster in acquiring cross-curricular competences.